Activation of Positive Cooperativity by Size‐Mismatch Assembly via Inclination of Guests in a Single‐Site Receptor. Issue 7 (21st February 2022) - Matsuno, Taisuke; Takahashi, Kanato; Ikemoto, Koki; Isobe, Hiroyuki
Abstract: A halogenated bowl‐shaped guest, corannulene, was encapsulated in a cylindrical host, [4]cyclochrysenylene, to form a bowl‐in‐tube complex, which mimicked supramolecular complexes between bowl guests and carbon nanotubes. As was the case with carbon nanotubes, the cylindrical space of [4]cyclochrysenylene trapped multiple corannulene molecules in an array, and 1 : 2 complexes were commonly obtained with the corannulene guests with various halogen substituents (F, Cl, Br and I). Careful statistical analyses of isothermal titration calorimetry data succeeded in revealing the stoichiometry, and the molecular structures of the 1 : 2 complexes were further clarified by X‐ray crystallographic analyses. Two fluorinated corannulene guests were stacked perpendicular to the cylinder axis, while two chlorinated guests were stacked with inclined orientations. The structural difference resulted in a large difference in the cooperativity of the two‐stage association in solution: fluorinated corannulene guests showed negative cooperativity for the 1 : 2 complexation, and the other, larger halogenated corannulene guests showed positive cooperativity. Abstract : Positive cooperativity was activated by mismatches of sizes between a host and guests. A larger guest thus recruited a second guest at the same cylindrical space of the host, assembling via inclinations in a single‐site receptor. Encapsulation behaviors of carbon nanotubes are deepened by this study with molecular entities.